Afetividade e o processo de ensino aprendizado na educação infantil: qual sua influência? - SILVA, Jamily Costa e (2022)
The present research proposal discusses the importance and contribution of affectivity in the teaching-learning process, with the objective of reflecting on the relevance and the way that affectivity influences the teaching-learning process. The methodology used was a qualitative research, of an explanatory nature, of a bibliographic nature, with surveys in Course conclusion works and articles, as well as in the Law of Guidelines and Bases of Brazilian Education (LDB 9394/96) and in the National Curricular Common Base (BNCC), through an electronic resource. In this way, this study provides important concepts for understanding the concept of affectivity and perspectives of its influence on early childhood student learning, given that it is a mediating aspect for the child's cognitive development, because through the study it was possible to perceive that affectivity it is the pillar of the teacher-student relationship capable of strengthening the pedagogical practice, so that the student has the scope of efficient learning. As well, it grants conceptions for educators to know their students not only in the cognitive aspect, but also, and mainly, in the affective-emotional aspect, in addition to scientific knowledge, making the educational action effective.